2019
DOI: 10.1016/j.afjem.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic ocular lens dislocation

Abstract: Introduction Ocular lens dislocation is a relatively rare and difficult to diagnose disorder. Computed tomography often confirms the diagnosis, however may be unavailable in resource limited settings. Bedside ultrasound offers an alternative method of diagnosis which is rapid, inexpensive, and relatively easy. Case A 59-year-old man presented with a complaint of decreased vision in his right eye after being assaulted. Exam was remarkable for decreased visual acuity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It is the most common cause of lens luxation-subluxation, accounting for about 53% of all cases [ 7 ]. Blunt ocular trauma compresses the eye in the anterior-posterior direction expanding the eye and stretching the zonules [ 8 ]. The direction of dislocation determines management.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common cause of lens luxation-subluxation, accounting for about 53% of all cases [ 7 ]. Blunt ocular trauma compresses the eye in the anterior-posterior direction expanding the eye and stretching the zonules [ 8 ]. The direction of dislocation determines management.…”
Section: Discussionmentioning
confidence: 99%
“…Lens dislocation alone is caused by multifactorial factors, including some kind of congenital abnormalities, such as Marfan syndrome, Weill-Marchesani syndrome, and homocystinuria, zonules-related eye disease, such as high myopia and pseudoexfoliation syndrome, iatrogenic condition, along with blunt trauma. [11], [12] A study reported that the major cause of lens dislocation was trauma. [12] Blunt trauma causes compression of the eye antero-posteriorly which then cause an expansion of the eye in several directions, laterally, superiorly, and inferiorly.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may present with pain in the affected eye, blurry vision, or vision loss [ 3 ]. The treatment of lens dislocation depends on the direction of lens displacement [ 3 , 12 ]. Anterior lens dislocations require emergent surgical correction if causing acute angle-closure glaucoma, whereas posterior lens dislocations can be managed by ophthalmology on an urgent basis [ 3 , 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of lens dislocation depends on the direction of lens displacement [ 3 , 12 ]. Anterior lens dislocations require emergent surgical correction if causing acute angle-closure glaucoma, whereas posterior lens dislocations can be managed by ophthalmology on an urgent basis [ 3 , 10 , 12 ]. Failure of conservative management or development of complications such as uveitis or glaucoma indicates the need for surgical correction of a posterior lens dislocation [ 3 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation